Teachers' Perceptions of the Challenges and Impacts of Utilizing Artificial Intelligence (AI) in English Language Teaching - Islahul Amal (Universitas Negeri Surabaya, 2025)
This study explores English teachers’ perceptions and lived experiences in utilizing Artificial Intelligence (AI) tools at SMPN 1 Mojowarno, a rural junior high school in Jombang. Guided by Max van Manen’s hermeneutic phenomenology and the TPACK framework, this study used semi-structured interviews with four English teachers to uncover the essence of their experiences. Findings reveal a significant tension in teachers' perceptions. While they acknowledged AI tools like ChatGPT and Canva could enhance learning efficiency and innovation, they also harboured deep concerns over AI's potential to disrupt human relationships, foster student dependency, and erode critical thinking, alongside fears of professional devaluation. Teachers' emotional responses were not static, evolving over time from initial curiosity to a more profound sense of caution and responsibility. This evolution was driven by significant challenges. Beyond technical issues like unstable infrastructure and gaps in digital competency due to limited training, teachers grappled with the inappropriateness of some AI content for their local cultural context. These pressures ultimately forced them into burdensome new roles as